The Effect of Centella (Centella asiatica (L.) Urb.) Extract with Several Types of Solvents as a Biostimulant on the Growth of Pagoda Mustard (Brassica rapa var. narinosa L.) - Jelita Putri Adisti; Suwirmen Suwirmen; Muhammad Idris (Universitas Andalas, 2023)
Biostimulants are natural organic compounds that can be applied to plants, so that they can modify plant physiology, stimulate growth and increase response to biotic and abiotic stresses. Biostimulants must have good solubility in suitable solvents. The research about the Effect of Centella (Centella asiatica (L.) Urb.) Extract with Several Types of Solvents as a Biostimulant on the Growth of Pagoda Mustard (Brassica rapa var. narinosa L.) was conducted from March to June 2022 at the Plant Physiology Laboratory and Greenhouse, Department of Biology, Faculty of Mathematics and Natural Sciences, Andalas University, Padang. The research aims to determine the effect of C. asiatica extract with several types of solvents as a biostimulant and to determine the best type of solvent to extract C. asiatica as a biostimulant in increasing the growth of Pagoda mustard. This study used a completely randomized design (CRD) consisting of 5 treatments with 6 replications. The treatment consist of control, distilled water, methanol, ethanol and acetone. The results obtained in this study were C. asiatica extract with several types of solvents gave significantly different effects on the parameters of leaf number, leaf area and leaf chlorophyll content. The results of this study indicate that methanol and ethanol are the best solvents for making C. asiatica extract as a biostimulant that can increase the growth of Pagoda mustard.